ENHANCING CONTENT DELIVERY WITH EDGE COMPUTING IN MEDIA AND ENTERTAINMENT - Sachin Gupta, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores the transformative impact of edge computing on content delivery in the media and entertainment industry. It examines the limitations of traditional content delivery networks (CDNs) and how edge computing addresses these challenges by reducing latency, improving scalability, and enabling new interactive experiences. The article discusses the technical architecture of edge computing solutions, implementation strategies, and real-world case studies from industry leaders like Netflix and Akamai. It also delves into the benefits of edge computing, including improved user experience, cost efficiency, and personalized content delivery. The article addresses challenges such as infrastructure investment, data security, and standardization, while highlighting future trends and opportunities in the convergence of edge computing with 5G networks and AI technologies. Throughout, it emphasizes the potential of edge computing to revolutionize content delivery and create new possibilities for media consumption and user engagement